Masonry mortar tool / Muhamad Anas Danish Zulkarnain, Muhammad Farez Fahmi Harith & Ruszaidee Rusli - Zulkarnain, Muhamad Anas Danish; Harith, Muhammad Farez Fahmi; Rusli, Ruszaidee
The designed prototype for this project is considerably seems as a successful build or project. It fulfilled every criterion set by faculty of Mechanical Engineering, UiTM Pasir Gudang which focus on the innovations and inventions that can be used as a construction tool. Besides that, it also fulfilled the criteria of team members which the main task is to have a convenient and reliable model for teaching and make spreading the masonry. The prototype is built due to the lack of understanding of the true meaning of mechanical engineering among students specifically thus looking in striving for a better and new knowledge also experience for Mechanical Engineering students. Here are the stated some the pros and cons obtained through the process of making the project.